Focus on Triple-Negative Breast Cancer: Potassium Channel Expression and Clinical Correlates - Lastraioli, Elena (Frontiers in Pharmacology, 2020)
Despite improvements in early diagnosis and treatment, breast cancer is still a major health problem worldwide. Among breast cancer subtypes, the most challenging and harder to treat is represented by Triple Negative molecular subtype. Due to its intrinsic features this subtype can’t be treated neither with hormonal therapy (since it does not express estrogen or progesterone receptors) nor with Epidermal Growth Factor Receptor 2 (HER2) inhibitors (as it does not express high levels of this protein). For these reasons, the standard of care for these patients is represented by a combination of surgery, radiation therapy and chemotherapy. In this scenario, searching for novel biomarkers that might help both in diagnosis and therapy is mandatory. In the last years it was shown that different families of potassium channels are overexpressed in primary breast cancers. The altered ion channel expression may be useful for diagnostic and therapeutic purposes due to some peculiar characteristics of this class of molecules. Ion channels are defined as pore-forming transmembrane proteins regulating passive ion fluxes in the cells. Ion channels represent good potential markers since, being localized at the plasmamembrane level, their detection and block with specific drugs and antibodies might be fast and tunable. This review focuses on triple negative breast cancers and recapitulate the current knowledge about potassium channels’ clinical relevance and their potential use in the clinical setting, for triple negative breast cancer diagnosis and therapy.